BERRIASIAN DROWNING OF THE PLASSEN CARBONATE PLATFORM AT THE TYPE-LOCALITY AND ITS BEARING ON THE EARLY EOALPINE OROGENIC DYNAMICS IN THE NORTHERN CALCAREOUS ALPS (AUSTRIA) - Gawlick H.-.; Schlagintweit F. (My University, 2006)
The Plassen carbonate platform (Kimmeridgian to Early Berriasian) developed above the Callovian to Tithonian carbonate clastic radiolaritic flysch basins of the Northern Calcareous Alps during a tectonically active period in a convergent regime. Remnants of the drowning sequence of the Plassen Formation have been discovered at Mount Plassen in the Austrian Salzkammergut. It is represented by calpionellid-radiolaria wacke- to packstones that, due to the occurrence of Calpionellopsis oblonga (Cadisch), are of Late Berriasian age (oblonga Subzone). Thus, the Plassen Formation at its type-locality shows the most complete profile presently known, documenting the carbonate platform evolution from the initial shallowing upward evolution in the Kimmeridgian until the final Berriasian drowning. The shift from neritic to pelagic sedimentation took place during Berriasian times. A siliciclastic-influenced drowning sequence sealed the highly differentiated Plassen carbonate platform. The former interpretation of a Late Jurassic carbonate platform formed under conditions of tectonic quiescence cannot be confirmed. The onset, evolution and drowning of the Plassen carbonate platform took place at an active continental margin. The tectonic evolution of the Northern Calcareous Alps during the Kimmeridgian to Berriasian time span and the reasons for the final drowning of the Plassen carbonate platform are to be seen in connection with further tectonic shortening after the closure of the Tethys Ocean.
Keywords: NORTHERN CALCAREOUS ALPS; PLASSEN CARBONATE PLATFORM; BERRIASIAN DROWNING; Berriasian; Tithonian; Kimmeridgian; Callovian; Mesozoic::Cretaceous::Lower::Berriasian; Мезозой::Меловая::Нижний::Берриасский; Mesozoic::Jurassic::Upper::Tithonian; Мезозой::Юрская::Верхний::Титонский; Mesozoic::Jurassic::Upper::Kimmeridgian; Мезозой::Юрская::Верхний::Киммериджский; Mesozoic::Jurassic::Middle::Callovian; Мезозой::Юрская::Средний::Келловейский